The Left Atrial Appendage Revised - Evora,Paulo Roberto Barbosa (2017)
Abstract Nonvalvular atrial fibrillation is associated with a 4- to 5-fold strokes increase and may be responsible for 15% to 20% of all strokes in the elderly. In this scenario, the left atrial appendage thrombus would be the associated with 90% of cases. The use of anticoagulants, percutaneous devices, and the left atrial appendage surgical exclusion is still an open discussion. For left atrial appendage procedures, relevant anatomic spatial relationships have to be emphasized, besides the chance of the normal physiological functioning would be eliminated with the proceedings. There are evidences that the left atrial appendage closure during routine cardiac surgery is significantly associated with an increased risk of early postoperative atrial fibrillation. Therefore, the purpose of this review is to focus basic aspects for continuous medical education. In summary, the rationale of this text is to emphasize anatomical and pharmacological aspects involved in the simple surgical exclusion of left atrial appendage under cardiopulmonary bypass. There are several operative techniques, but to conclude this revision it will present one of them based on the discussed basic sciences.